Online Relationship Marketing - Steinhoff, Lena; Arli, D.; Weaven, S.; Kozlenkova, I. V. (Journal of the Academy of Marketing Science)

Enhancing Loyalty Program Effectiveness by Stimulating Member Activity along the Customer Journey - Steinhoff, Lena; Zondag, M. (Proceedings of the 48th European Marketing Academy (EMAC) Conference, Hamburg)

Inklusion aus der Sicht von Kindern mit dem Förderschwerpunkt Lernen – Überprüfung von Messinvarianz in verschiedenen schulischen Kontexten. - Knickenberg, Margarita; Zurbriggen, Carmen; Schwab, Susanne; Gebhardt, Markus

Students with emotional or behavioral problems: Their emotional experience in the classroom during peer interactions. - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin

Individual and institutional determinants for primary school teachers’ self-efficacy beliefs regarding inclusive education – Results from qualitative interviews. - Knickenberg, Margarita; Frank, Hellmich; Marwin Felix, Löper

Potential influencing factors for teachers’ self-efficacy beliefs concerning inclusive education - Knickenberg, Margarita; Marwin Felix, Löper; Frank, Hellmich

Assessing social interaction quality with the Experience Sampling Method - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin

Peer interactions in everyday school life versus leisure time of adolescents and their emotional experience. - Knickenberg, Margarita; Zurbriggen, Carmen; Hinni, Chantal; Venetz, Martin

Erfassung von Merkmalen inklusiven Unterrichts mit der Experience Sampling Method. - Knickenberg, Margarita; Zurbriggen, Carmen

Applicability of ESM in School: Quality of students' social interaction - Knickenberg, Margarita; Chantal, Hinni

Das gesungene Lied im Religionsunterricht - zwischen Ritualisierung und Instrumentalisierung - Hoyer, Isabelle; Kohlmeyer, Theresa (Praxis des RU)

Inklusion vom Kind aus denken: Mit der KrafT Bildungsdokumentation den Übergang Kita-Grundschule gemeinsam gestalten. Workshop im Rahmen des 8. Paderborner Grundschultages. Universität Paderborn - Büker, Petra; Meier, Stefanie; Ogrodowski, Jana; Seibel, Melanie; Weiß, Christine
Angegebener Monat: März 2019

Kriterien für eine qualitätsvolle Übergangsgestaltung: Wie können Kinder, pädagogische Fachkräfte und die Übergangsgestaltung von der Kooperation profitieren? Eröffnungsvortrag zum Fachtag: „Kriterien für eine qualitätsvolle Übergangsgestaltung“ im Bildungshaus Emmerthal (Niedersachsen) - Büker, Petra; Ogrodowski, Jana
Angegebener Monat: Mai 2019

Das moralische Urteil von Schülerinnen und Schülern mit Verhaltensstörungen. Theoretische Ansätze und empirische Befunde aus kohlbergianischer und neo-kohlbergianischer Perspektive - Aschhoff-Hartmann, Stefanie

Montesquieu, Zeitschrift für Didaktik der Philosophie und Ethik

Montesquieu und die Philosophiedidaktik - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Alfred J. Noll: Absolute Mäßigung. Montesquieu und sein L‘ esprit des loix. Köln: PapyRosa 2018. 1020 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Der Mythos der Gewaltenteilung und die Metaphorik des Kräftepolygons bei Montesquieu - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Common Notions in Early Modern Thought. (Journal of Early Modern Studies)

Arguing from Presumptions. Essays on Early Modern Ethics and Politics - Blank, Andreas